Effects of high-fat diet-induced obesity on sperm small RNA profile and offspring phenotype in mice - Hajati, Fatemeh (My University, 2022)
Paternal obesity has not only adverse effects on exposed individuals, but it can also induce metabolic changes in offspring through epigenetic inheritance. High-fat diet (HFD) affects sperm’s small non-coding RNA (sncRNA) levels, serving as a potential transmitter of acquired paternal obesity to the next generation. It is unclear which part of the reproductive tract has the main contribution to sperm sncRNA changes and whether these changes can be reversed by treating obesity. To answer these questions, C57BL/6 adult male mice were fed with an HFD for eight weeks to induce obesity. Control mice were fed a chow diet throughout the whole experiment. HFD-induced obese mice were then treated with a healthy diet, metformin medication, or exercise. Before sacrifice, males were mated with females to generate F1. Subsequently, sperm and different parts of the reproductive tract were collected to assess sncRNA expression patterns by deep sequencing. Results indicated that diet and exercise interventions significantly decreased weight and fat mass, while metformin medication only diminished gaining weight. Obesity of fathers (F0) did not significantly affect the growth and weight of offspring (F1). However, the fat mass of female offspring of HFD fathers was slightly reduced compared to progeny of chow fathers. RNA extraction from sperm, efferent ducts, and different parts of the epididymis resulted in good quality RNA with high integrity values. RNA sequencing of these samples will reveal interesting novel information on the HFD-induced changes in small RNAs throughout the male reproductive tract and the effects of interventions on sperm sncRNA profiles.
Keywords: Epigenetic, Metabolic disease, sncRNA, High-fat diet